Mechanical characterization of an ecomaterial: Case of compress earth bloc (CEB) with addition of cotton waste - TOUKOUROU, CHAKIROU A.; FAGLA, FANOU ZINSOU BENOÎT; BAGAN, GONTRAND COMLAN; ADJOVI, Loko; AVAMASSE, SEFIOU (My University, 2015)
This work studies the prospect of incorporation of cotton waste in the CEB. This study, prompted by the desire to reduce the cost of construction as well as reducing the weight of CEB incorporating their low density materials such as cotton waste, fits well with the policy of promotion and development of local building materials Benin. This work is focused on the determination of mechanical properties of composite: soil–cement-waste cotton material. First, we characterized the land of study. Characterization tests in the laboratory were used to classify the material according to the classification of the standard NF P 11 300 and the GTR. These tests, our study are a land of clay - sand mixture, which contains a high proportion of fines. Its plasticity index is adequate for achieving the CEB. Then, with the addition of CEB cotton waste percentages 10%, 20 %, 30 %, 40% and 50% were tested for simple compression, 3-point bending, abrasion and water absorption capillarity. The incorporation rate which provide the best mechanical resistance levels are 10 % and 20 %. For these rates, unconfined compressive strength at 21 days of age blocks are respectively 3.30 MPa and 3.01 MPa, their flexural strength three points are respectively 0.76 MPa and 0.70 MPa. Moreover, the comparative study between the test results for the CEB with the addition of cotton waste and those without adding simply stabilized cement revealed that CEB with the addition of cotton waste to 21 days of age are slightly less durable and less porous than simply stabilized. The resistance values obtained allows us to affirm that the use of CEB with the addition of cotton waste is possible in light constructions.
Keywords: CEB; mechanical properties; cotton waste; simple compression; three-point bending